Optimal Monopolist Pricing Under Demand Uncertainty in Dynamic Markets - Raman, Kalyan; Chatterjee, Rabikar (Management Science, 1995)
We examine pricing policy for a monopolist facing uncertain demand in a market characterized by dynamics on the demand side (such as diffusion or saturation effects) and/or on the cost side (experience curve effects). Our model explicitly incorporates the impact of demand uncertainty, and thus allows us to analyze the implications of uncertainty on the optimal price path, by contrasting the stochastic policy with the corresponding deterministic policy. We begin with an analysis of the general model and then focus on several special cases based on well known demand specifications to gain more specific insights and to suggest directional guidelines for dynamic pricing decisions in an uncertain environment. In general, the interaction among uncertainty, demand and/or cost dynamics, and firm's discount rate. Thus, farsighted firms operating under dynamic market conditions with high demand uncertainty, such as high tech companies with innovative products for consumer or industrial markets, should attach particular importance to the formal consideration of uncertainty in their long term pricing decisions.